MR volumetric study of cerebellum related to age ang sex - Wan Ahmed, Wan Aireene (2015)
Introduction: The advancement of MRI techniques has open up many neuroanatomical studies of normal brain growth and atrophy. Numerous neurological and neuropsychiatric disorders, which can cause changes in cerebellum volumes have been identified particularly epilepsy, schizophrenia, Alzheimer’s dementia, depression and autism among others. Investigations of aging effects on the cerebellum are important, not only to understand normal aging process, but also for comparative study of the pathophysiology of degenerative brain disorders. Sex differences in gross cerebellar neuroanatomy have been observed in several studies. Currently there is no normative data of MR cerebellum volumetry available for Malaysian population. Objectives: The general objective for this study is to determine the age and sex difference of the volume of cerebellum in healthy volunteers. Methods and materials: This was a cross sectional study involving 164 subjects who underwent MRI. The age of the subjects ranged from 7 to 77 years old. MRI was performed using Signa Horison LX 1.0 Tesla scanner by General Electric. MRI images were obtained in T1 sagittal sections with 5milimeter thickness with 2-millimeter gap. Cerebellum volumes were measured using manually traced slice volumetry method. The mean (SD) of total cerebellum volume was calculated and analyzed using IBM SPSS version 20. Anatomical boundaries for cerebellum volumetry done with manual tracing. Normalization of cerebellum volume with intracranial volume was done by using co-variance methods introduced by Jack et al. (1989). Manual tracing using alternate slice method was utilized in obtaining intracranial volume as described by Eritaia et al. (2000). Image display and manual tracing of the cerebellum and intracranial areas were performed using Osirix software ver.3.7.1 (Pixmeo Sarl). Data was compiled and analyzed using PASW Statistic ver.18 (SPSS Inc.). Results: The overall mean normalized cerebellar volume is 181.1 ± 24.8 cm3. When analyzed separately among gender, normalized cerebellar volume was significantly higher in male (p value= 0.035; 95% +- CI). There is a statistically significant negative correlation between age and total cerebellum volume (r is - 0.492). Cerebellar volume becomes smaller at older age with moderate to good correlation. Conclusion: The study provided a reference data of cerebellar volumes in original and normalized formats for normal Kelantan population for a valuable reference in many physiological and pathological conditions for local population. The mean normalized cerebellar volume was statistically significant in genders with larger volumes in male subjects. They also had larger intracranial volumes than female. There is significant relationship between normalized cerebellum volume with age.